Relationship Between Selected Personal Variables and Academic Performance of Secondary School Students in Kenya. - Ogalo., Dishon, A. (JOOUST, 2018)
Academic performance among students in developed countries has been of great concern. In USA for instance child education and academic performance in general form integral parts of its national development In Africa, academic performance of students aids career decision making amongst them. In Kenya for instance, academic performance amongst students is the foundation of their future careers. However, there has been low academic performance of secondary school students in Rongo Sub County, which has negatively influenced the career choices of the students from the Sub County. Students in most cases are not able to pursue careers of their choices due to low entry grades. The purpose of the study was therefore to determine the relationship between selected personal variables and academic performance of secondary school students in Rongo Sub County. The objectives of the study were: To find out the relationship between self-concept and academic performance, to establish the relationship between self-efficacy and academic performance, to examine the relationship between intrinsic motivation and academic performance and to determine the relationship between self-esteem and academic performance. The Person-Cantered Theory of Rogers was used to inform the study. A sequential explanatory research design was employed with a population of 2229 form four students from 7 Public Secondary Schools, 23 teacher counsellors from 23 Public Secondary Schools. A sample size of 223 forms four students, 23 teacher counsellors in 7 Public Secondary schools. Simple random sampling was used to select student participants; stratified sampling was used to select secondary schools to be studied while saturated sampling was used to select teacher counsellors. A questionnaire with four parts: Academic Self-Concept of students, Academic Self-Efficacy of students, Academic Self-Esteem of students and Academic Intrinsic Motivation of students was used to collect quantitative data while qualitative data was collected using interview schedules for teacher counsellors. Validity of the questionnaires was ensured through expert judgment by university lecturers while reliability of the questionnaire was ensured through Cronbach alpha and a reliability coefficient of r= 0. 7513 was reported. Trustworthiness of qualitative data was ensured through adoption of well-established research methods. Quantitative data was analysed using Pearson Correlations. Qualitative data from interviews was analysed using Thematic Analysis. In the first objective, the results indicated a strong positive relationship of r = 0.794 between self-concept and students' academic performance; In the second objective, a strong positive relationship of r = 0.814 between self-efficacy and students' academic performance was reported; In the third objective a positive relationship of r = 0.627 between intrinsic motivation and students' academic performance was reported while in the fourth objective, a strong positive relationship of r = 0. 768 between self-esteem and students' academic performance was reported. It was concluded that self-concept, self efficacy, intrinsic motivation and self-esteem had a positive relationship with academic performance. Teacher counsellors should utilize appropriate therapy techniques to help students with negative and low self-aspects to improve in academic performance. The Teachers Service Commission -Kenya can use the findings to advice its teachers on the best ways of handling learners in order to motivate them to achieve their full academic potentials.
Keywords: Selected Personal Variables.; Academic Performance .; Secondary School Students.; Kenya.